Influence of temperature and plasma parameters on the properties of PEALD HfO2 - Lapteva, Margarita; Beladiya, Vivek; Riese, Sebastian; Hanke, Phillip; Otto, Felix; Fritz, Torsten; Schmitt, Paul; Stenzel, Olaf; Tunnermann, Andreas; Szeghalmi, Adriana (Optical Materials Express, 2021)
HfO2 has promising applications in semiconductors and optics due to its high dielectric constant and high refractive index. In this work, HfO2 thin films were deposited by plasma enhanced atomic layer deposition (PEALD) using tetrakis-dimethylamino hafnium (TDMAH) and oxygen plasma. The process optimization to obtain high quality HfO2 thin films with excellent uniformity over a 200 mm diameter is thoroughly discussed. The effects of deposition temperature and plasma parameters on the structural, mechanical, and optical properties, and the chemical composition of the films were investigated. Optimized process parameters yielding a high refractive index, high density, low impurities, low OH incorporation, low absorption in the UV spectral range, and high laser-induced damage threshold (LIDT) were selected for antireflection coatings. The HfO2 thin films were incorporated into antireflection coatings designed for the fundamental wavelength at 1064 nm and its higher harmonics up to the 4th order.
CRIS-Team Scopus Importer:2023-04-20